2013
DOI: 10.1124/dmd.113.055525
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Cytokine-Dependent Regulation of Hepatic Transporters and Bile Acid Homeostasis during Infectious Colitis in Mice

Abstract: Various disease models have been shown to alter hepatic drugmetabolizing enzyme (DME) and transporter expression and to induce cholestasis through altered enzyme and transporter expression. Previously, we detailed the regulation of hepatic DMEs during infectious colitis caused by Citrobacter rodentium infection. We hypothesized that this infection would also modulate hepatic drug transporter expression and key genes of bile acid (BA) synthesis and transport. Mice lacking Toll-like receptor 4 (TLR4), interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
1
15
1
Order By: Relevance
“…Proportional increases of Gammaproteobacteria in IT-operated animals were a potential contributor of the observed increase in the levels of circulating bile acids (38). Another study which examined a colitis mouse model found that Citrobacterrodentium infection downregulated the genes involved in bile acid biosynthesis and transportation, and increased the risk of cholestasis (39). In our study, we also found a significantly increased levesl of Citrobacter in the ICP patient group.…”
Section: Discussionsupporting
confidence: 69%
“…Proportional increases of Gammaproteobacteria in IT-operated animals were a potential contributor of the observed increase in the levels of circulating bile acids (38). Another study which examined a colitis mouse model found that Citrobacterrodentium infection downregulated the genes involved in bile acid biosynthesis and transportation, and increased the risk of cholestasis (39). In our study, we also found a significantly increased levesl of Citrobacter in the ICP patient group.…”
Section: Discussionsupporting
confidence: 69%
“…This finding is well in line with the fact that treatment with recombinant Tnf-a, IL1-b, or IL-6 in C57BL/6 mice showed a transient or sustained down-regulation of different hepatic BA transporters such as Ntcp and Bsep 6,28 and Cyp7a1. 29 Furthermore, cytokine treatment had effects on mRNA expression of transcription factors with reduced Fxr expression after Tnf-a treatment. 30 In a recent study, Jahnel et al 23 analyzed hepatic tissue of DSS-treated mice (male BL6 mice received 3% DSS for 7 d) and did not observe any FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous studies have demonstrated poly I:C-mediated induction of pro-inflammatory cytokines both in vivo in the liver, placenta, and brain [15,36,37] and in vitro [38][39][40]. Several studies have also demonstrated IL-6 and TNF-α-mediated downregulation of drug transporters both in vivo [41,42] and in vitro [8,43]. We recently demonstrated that IL-6 and endotoxin-mediated downregulation of transporters in the liver is mediated by NF-κB and STAT3, which are key inflammation-induced transcription factors [2,44].…”
Section: Discussionmentioning
confidence: 99%